PERANAN BANK SAMPAH SEKOLAH DI KOTA PEKANBARU - Fitria, Melda; Ekwarso, Hendro; ', Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study is descriptive studyw hich aims to find up the role and the constrains faced of the school waste bank in the City of Pekanbaru. The samples are determined based on the purposive sampling.This study involved a sample of 20 Schools that have a waste bank. The data were collected through observations, documentations, and interviews. The data analyzed using the descriptive methode. The result show the role of school waste bank of implementations 3R program and people incomes still small. The role of waste management with School Waste Bank program with 3R consept is able to process waste by 9,7% of all the waste in 2013 is 133.500.260 kg of waste dumped into Muara Fajar lanfill. Role of School Waste Bank agains income from saving small trash, but the increase of the 2012 to the 2013 is Rp. 12.629.626,- up to Rp. 15.192.492,-. Constrains faced by the bank is waste due to a lack of socialization into school by the goverment and school have not been able to recycle waste that saved his own, so still rely use Central Waste Bank to prosess.Keywords: School Waste Bank, Role